2016
DOI: 10.1161/atvbaha.116.307825
|View full text |Cite
|
Sign up to set email alerts
|

Intermedin 1− 53 Attenuates Abdominal Aortic Aneurysm by Inhibiting Oxidative Stress

Abstract: Objective-Oxidative stress plays a critical role in the development of abdominal aortic aneurysm (AAA). Intermedin (IMD) is a regulator of oxidative stress. Here, we investigated whether IMD reduces AAA by inhibiting oxidative stress. Approach and Results-In angiotensin II-induced ApoE −/− mouse and CaCl 2 -induced C57BL/6J mouse model of AAA, IMD 1−53 significantly reduced the incidence of AAA and maximal aortic diameter. Ultrasonography, hematoxylin, and eosin staining and Verhoeff-van Gieson staining showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 48 publications
0
35
0
Order By: Relevance
“…For instance, in an animal model of Ang II‐induced hypertension, RAMP1 transgenic mice were shown to be protected from increases in their SBP 24 . However, the CGRP and/or CGRP receptor expression profile varies with the state and stage of the disease, including that in the Ang II‐induced model 25,26 . In addition, the change in CGRP receptor expression was suggested to further amplify the responses to CGRP, especially in the hypertension model 27 .…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in an animal model of Ang II‐induced hypertension, RAMP1 transgenic mice were shown to be protected from increases in their SBP 24 . However, the CGRP and/or CGRP receptor expression profile varies with the state and stage of the disease, including that in the Ang II‐induced model 25,26 . In addition, the change in CGRP receptor expression was suggested to further amplify the responses to CGRP, especially in the hypertension model 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Intermdedin1–53, a product of prepro-intermedin, reduced AngII or calcium chloride-induced AAA in mice. 78 This preventive effect on AAA was associated with attenuation of oxidative stress in AAA.…”
Section: Abdominal Aortic Aneurysmsmentioning
confidence: 97%
“…Our previous research showed that exogenous IMD1-53 may attenuate CKD-associated vascular calcification by upregulating α-klotho and vitamin D3 plus nicotine (VDN)-induced vascular calcification by increasing MGP in young rats [6,7]. In addition, IMD1-53 treatment could improve vascular function by increasing endothelial nitric oxide synthase activity [25] and inhibiting reactive oxygen species production [26], which may affect vascular aging [4]. However, whether IMD inhibits aging-associated vascular calcification is unclear.…”
Section: Introductionmentioning
confidence: 99%